1992
DOI: 10.1209/0295-5075/19/5/002
|View full text |Cite
|
Sign up to set email alerts
|

Crossover Between Tricritical and Critical Demixing Regimes of Polymer Solution: Small-Angle Neutron Scattering Data

Abstract: Using a small-angle scattering technique, we measured the temperature dependence critical (multicritical) point is approached by a nonisomorphous path.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
4
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…Accordingly, the critical index γ = 1.23 ± 0.02 for the susceptibility (i.e., the osmotic compressibility) in χ ∼ ( T − T C ) -γ at T ⇒ T C for all solutions studied agrees within experimental errors with the Ising model value (1.239 ± 0.002 12 ). The crossover takes place when ξ ∼ R g and thus reproduces the main features of the crossover observed in solutions of PS in CH- d (see the inset in Figure ). , These observations delineate an intrinsic analogy between the temperature behavior of polymers in SCFs and in liquid ϑ solvents in the vicinity of the UCST and show that polymer solutions in SCFs belong to the universality class of the Ising model.
1 ξ( T ) for h -PDMS with M W = 22 500 (▾), 47 700 (▴), and 79 900 (·).
…”
supporting
confidence: 74%
“…Accordingly, the critical index γ = 1.23 ± 0.02 for the susceptibility (i.e., the osmotic compressibility) in χ ∼ ( T − T C ) -γ at T ⇒ T C for all solutions studied agrees within experimental errors with the Ising model value (1.239 ± 0.002 12 ). The crossover takes place when ξ ∼ R g and thus reproduces the main features of the crossover observed in solutions of PS in CH- d (see the inset in Figure ). , These observations delineate an intrinsic analogy between the temperature behavior of polymers in SCFs and in liquid ϑ solvents in the vicinity of the UCST and show that polymer solutions in SCFs belong to the universality class of the Ising model.
1 ξ( T ) for h -PDMS with M W = 22 500 (▾), 47 700 (▴), and 79 900 (·).
…”
supporting
confidence: 74%
“…[3] in the mean field approximation which cannot reliably be used in the vicinity of the critical point. The distance between 0 and T c reflects the width of the crossover region from critical to tricritical.In our work [4] we have demonstrated that at the critical demixing point T c , polymer solutions must exhibit Ising-like critical behavior which is confirmed in [2]. The theory developed in [4] does not involve three-body interactions at the microscopic level; they appear, nevertheless, as fluctuation corrections to Flory-Huggins mean field theory [4,5].…”
supporting
confidence: 54%
“…(2) and (6) of [1] are taken from theories describing different critical regimes (e.g., see Ref. [2]): Equation (2) is valid in the tricritical region of the phase diagram (e.g., see Fig. 1 of [2]) while Eq.…”
mentioning
confidence: 99%
See 2 more Smart Citations